2005
DOI: 10.1016/j.febslet.2005.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids increase PGC‐1α expression in isolated rat islets

Abstract: PGC-1a mRNA and protein are elevated in islets from multiple animal models of diabetes. Overexpression of PGC-1a impairs glucose-stimulated insulin secretion (GSIS). However, it is not well known which metabolic events lead to upregulation of PGC-1a in the b-cells under pathophysiological condition. In present study, we have investigated effects of chronic hyperlipidemia and hyperglycemia on PGC-1a mRNA expression in isolated rat islets. Isolated rat islets are chronically incubated with 0, 0.2 and 0.4 mM olei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 53 publications
4
29
0
Order By: Relevance
“…Mice with muscle-specific overexpression of lipoprotein lipase, which increases fatty acid influx into skeletal muscle, display extensive mitochondrial proliferation (32). Fatty acids have also been shown to increase PGC-1␣ expression in muscle cells (33) and ␤-cells (34), and this is associated with increased mitochondrial metabolism (33,35). The fatty acid subtype appears to be important (33), as palmitate alone reduces PGC-1␣ expression (36); however, this may be related to its activation of inflammatory pathways that are known to impact on PGC-1␣ expression (37).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with muscle-specific overexpression of lipoprotein lipase, which increases fatty acid influx into skeletal muscle, display extensive mitochondrial proliferation (32). Fatty acids have also been shown to increase PGC-1␣ expression in muscle cells (33) and ␤-cells (34), and this is associated with increased mitochondrial metabolism (33,35). The fatty acid subtype appears to be important (33), as palmitate alone reduces PGC-1␣ expression (36); however, this may be related to its activation of inflammatory pathways that are known to impact on PGC-1␣ expression (37).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PGC-1α mediates the FFA-induced pancreatic β-cell apoptosis in the development of T2DM, a process known as 'lipotoxicity'. Zhang and coworkers demonstrated that there is a direct correlation between FFAs and PGC-1α (Zhang et al 2005). After 72-h incubation, elevated FFAs (oleate/palmitate) not only dose-dependently increase PGC-1α expression level in isolated islets but also increase PGC-1α mRNA level in isolated islets and in mouse β-cell-derived bTC3 cell lines.…”
Section: Pancreatic β-Cell Apoptosismentioning
confidence: 99%
“…Elevations of plasma fatty acids resulting from infusion of triglyceride emulsions caused downregulation of PPARG C1A and several nuclear-encoded mitochondrial genes in skeletal muscle of healthy human subjects [82]. As fatty acids induce PGC-1α in rat pancreatic islets [76], tissuespecific regulation of PPARGC1A expression by fatty acids can be implied. PPARGC1A and PPARGC1B expression was compared in muscle biopsies from young and elderly dizygotic and monozygotic twins, before and after insulin stimulation [83].…”
Section: Functional Studies In Humansmentioning
confidence: 99%
“…Ucp2 could have been another effector of PGC-1α upregulation, since enhanced beta cell UCP2 level/activity diminishes glucose-induced insulin secretion in both humans and animal models [73][74][75]. The upregulation of Ppargc1a expression in diabetic animal models is not understood, but fatty acids enhance Ppargc1a expression and impair beta cell function in rat islets [76]. Also, incomplete inactivation of FOXO1 may have contributed, as FOXO1 haploinsufficiency rescued beta cell failure in mice lacking the gene for insulin receptor substrate 2 (Irs2 −/− ) [77] and a gain-of-function FOXO1 mutation targeted to liver and beta cells enhanced hepatic gluconeogenesis and impaired beta cell compensation [78].…”
Section: Pgc-1α and Glucose Homeostasismentioning
confidence: 99%